The efficiency of natural and artificial pollinators in plantain (Musa spp. AAB group) hybridisation and seed production - Ortíz, R.; Crouch, J.H. (1997)
Plantain-derived tetraploid hybrids are routinely crossed In Musa breeding programmes with diploid Musa accessions for the efficient generation of putative triploid hybrid seed. However, natural open pollination of these same tetraploid hybrids also consistently generates viable seed. The mean germination rate of such open pollinated seed was observed to be higher than that of seed generated from artificial pollinations. This may suggest that tetraploid Musa hybrids played a much more important role in the evolution of triploid Musa landraces than previously considered. Moreover, the elite performance of certain hybrids generated through such open pollination offers possibilities of new Musa breeding paradigms. The inferences of these observation for Musa evolution and the implication for Musa breeding are discussed